Gastric Carcinosarcoma and 18F-FDG PET/CT. (November 2015) - Li, Beilei; Zhang, Yiqiu; Hou, Jun; Cai, Liang; Zhou, Jianwei; Shi, Hongcheng
Abstract : Abstract: Gastric carcinosarcoma is a rare, malignant neoplasm that simultaneously comprises mixed epithelial and mesenchymal elements. In the present study, we report a case of gastric carcinosarcoma composed of rhabdomyosarcoma and adenocarcinoma on 18 F-FDG PET/CT.